Mitochondrial and calcium perturbations in rat CNS neurons induce calpain-cleavage of Parkin: Phosphatase inhibition stabilizes pSer(65)Parkin reducing its calpain-cleavage - Wang, Hu (Biochim Biophys Acta Mol Basis Dis, 2019)
Mitochondrial impairment and calcium (Ca(++)) dyshomeostasis are associated with Parkinson’s disease (PD). When intracellular ATP levels are lowered, Ca(++)-ATPase pumps are impaired causing cytoplasmic Ca(++) to be elevated and calpain activation. Little is known about the effect of calpain activation on Parkin integrity. To address this gap, we examined the effects of mitochondrial inhibitors [oligomycin (Oligo), antimycin and rotenone] on endogenous Parkin integrity in rat midbrain and cerebral cortical cultures. All drugs induced calpain-cleavage of Parkin to ~36.9/43.6 kDa fragments. In contrast, treatment with the proinflammatory prostaglandin J2 (PGJ2) and the proteasome inhibitor epoxomicin induced caspase-cleavage of Parkin to fragments of a different size, previously shown by others to be triggered by apoptosis. Calpain-cleaved Parkin was enriched in neuronal mitochondrial fractions. Pre-treatment with the phosphatase inhibitor okadaic acid prior to Oligo-treatment, stabilized full-length Parkin phosphorylated at Ser(65), and reduced calpain-cleavage of Parkin. Treatment with the Ca(++) ionophore A23187, which facilitates Ca(++) transport across the plasma membrane, mimicked the effect of Oligo by inducing calpain-cleavage of Parkin. Removing extracellular Ca(++) from the media prevented oligomycin- and ionophore-induced calpain-cleavage of Parkin. Computational analysis predicted that calpain-cleavage of Parkin liberates its UbL domain. The phosphagen cyclocreatine moderately mitigated Parkin cleavage by calpain. Moreover, the pituitary adenylate cyclase activating peptide (PACAP27), which stimulates cAMP production, prevented caspase but not calpain-cleavage of Parkin. Overall, our data support a link between Parkin phosphorylation and its cleavage by calpain. This mechanism reflects the impact of mitochondrial impairment and Ca(++)-dyshomeostasis on Parkin integrity and could influence PD pathogenesis.